Manganese buffer induced high-performance disordered MnVO cathodes in zinc batteries. Issue 7 (26th May 2021) - Wei, Shiqiang; Chen, Shuangming; Su, Xiaozhi; Qi, Zhenghang; Wang, Changda; Ganguli, Babu; Zhang, Pengjun; Zhu, Kefu; Cao, Yuyang; He, Qun; Cao, Dengfeng; Guo, Xin; et al.
Abstract : A significant buffer effect from manganese ions is discovered to tune the atomic structure and valence state of an electrode material, resulting in a high-performance zinc battery. Abstract : Buffer reactions can prevent changes induced by external causes. Here, we demonstrate the significant buffer role of a very small amount of Mn in a self-optimized cathode for an aqueous Zn-ion battery. Our operando X-ray characterization studies reveal that the dissolution of most of the Mn in MnV2 O4 during the first charging cycle induces atomic re-arrangement to form a disordered vanadium oxide phase with 0.88 at% Mn. Interestingly, the residual Mn ions exhibit voluntary migration between tetrahedral and octahedral sites during Zn 2+ de/intercalation. This Mn migration not only stabilizes the main structure of the vanadium-based electrode, but also modulates the Fermi surface of V 3d against excessive drift. As result, the optimized cathode delivers an excellent capacity of 610.2 mA h g −1 at 0.2 A g −1 and long-term cycling stability over 4000 cycles. This buffer contribution via tunable metal ions exhibits high potential for applications in long-life metal-ion batteries and related fields.